A NETWORK META-ANALYSIS: EFFICACY AND SAFETY OF ROTATIONAL ATHERECTOMY, ORBITAL ATHERECTOMY, AND INTRAVASCULAR LITHOTRIPSY COMPARISONS FOR NODULAR CORONARY LESIONS IN PERCUTANEOUS CORONARY INTERVENTION - Handayani, Riana; Oktaviono, Yudi Her; Suryawan, I Gde Rurus; Susilo, Hendri; Aziz, Karimah Khitami; Erwan, Nabila Erina (Folia Medica Indonesiana, 2025)
Percutaneous Coronary Intervention (PCI) has continued to evolve since its introduction in 1977. Currently, 12% of all PCI procedures for coronary artery stenosis involve Calcified Nodules (CN). CN is defined as nodular calcification that protrudes into the lumen of the coronary artery. In this era, improving the feasibility and success of PCI is essential through the use of advanced techniques, innovative approaches, and specialized devices in coronary interventions. These techniques include Rotational Atherectomy (RA), Orbital Atherectomy (OA), and Intravascular Lithotripsy (IVL). Comparisons of RA, OA, and IVL are still being extensively studied in terms of their effectiveness and safety in treating complex lesions such as CN. Given the high costs of these devices, this Network Meta-Analysis (NMA) was conducted to evaluate and compare the efficacy and safety of RA, OA, and IVL based on recent studies. The primary analysis in this study was performed using MetaInsight V6.1.1, presenting odds ratios (OR) based on a Bayesian Network Meta-Analysis and ranking the interventions according to the Surface Under the Cumulative Ranking Curve (SUCRA). The primary outcomes assessed were efficacy and safety. Efficacy was defined as the procedural success rate, and safety as the overall safety rate of each procedure. Secondary outcomes included periprocedural complications (dissection, perforation, slow flow/no-reflow, cardiac tamponade, and device failure), as well as the incidence of major adverse cardiovascular events (MACE) within 30 days. The analysis revealed a statistically significant difference in efficacy between IVL and RA, favoring IVL (OR 2.66, 95% CrI: 1.27, 6.16). However, no statistically significant differences were observed in other primary or secondary outcomes among RA, OA, and IVL. Based on SUCRA rankings, OA was the most effective in preventing MACE, while RA showed the lowest risk of periprocedural complications. Nevertheless, this network meta-analysis has several limitations due to the uncertainty of the available data. Further research, including randomized controlled trials (RCTs) or larger cohort studies with direct comparisons of all three techniques (closed-loop designs), is warranted to validate these findings.